Mass spectrometry imaging in food analysis - Nollet, Leo M. L. 1948- (Food analysis & properties, 2020)
"Mass Spectrometry Imaging in Food Analysis, a volume in the Food Analysis and Properties Series, explains how the novel use of matrix-assisted laser desorption/ionization mass spectrometry imaging (MALDI-MSI) will be an ideal complementary approach. MALDI-MSI is a two-dimensional MALDI-MS technology that can detect compounds in a tissue section without extraction, purification, separation, or labeling. It can be used to visualize the spatial distribution of biomolecules in foods."